Baltic amber teething necklaces: could succinic acid leaching from beads provide anti-inflammatory effects? - Michael D. Nissen; Esther T. L. Lau; Peter J. Cabot; Kathryn J. Steadman (BMC, 2019)
Abstract Background Baltic amber teething necklaces have been popularized as a safe and natural alternative to conventional or pharmacological medicines for the management of teething pain. However, claims made by retailers regarding the efficacy and mechanism of action of these necklaces lack scientific or clinical basis. The claim most closely resembling science is the assertion that succinic acid will leach out of the beads and through the skin of the wearer and carry out anti-inflammatory and analgesic effects. The objective of the current research is to scientifically assess this claim. Methods Beads from necklaces were powdered for identification by infrared spectroscopy, and dissolved in sulfuric acid for quantification of succinic acid using HPLC. Succinic acid release from beads was assessed by long-term submersion of amber beads (separated according to light, medium and dark brown colour) in solvents relevant to human skin conditions. The potential for succinic acid to have anti-inflammatory effects was assessed by measuring the release of inflammatory cytokines IL-1α, IL-1β, IL-8 and TNFα, and the inflammatory messenger PGE2, from THP-1 human macrophages after treatment with succinic acid and LPS. Results Amber teething necklaces were positively identified as Baltic amber, by comparison of the beads' infrared spectrum to the literature, and by their succinic acid content (1.5 mg per bead; 1.44% w/w). However, whole amber beads submerged in octanol or pH 5.5 phosphate buffered saline did not release any measurable succinic acid, except for the light-coloured beads in octanol which broke into tiny fragments. Additionally, treatment of macrophages with succinic acid did not reduce the release of any inflammatory cytokines measured, and displayed toxicity to the cells at high concentrations. Conclusions While amber teething necklaces are genuine Baltic amber, we have found no evidence to suggest that the purported active ingredient succinic acid could be released from the beads into human skin. Additionally, we found no evidence to suggest that succinic acid has anti-inflammatory properties.